Antiproliferative Triterpenoid Saponins from the Stem of Psychotria sp. - Zhang, Cui-Xian; Zhang, Dong-Mei; Chen, Min-Feng; Guan, Shan-Yue; Yao, Jun-Hua; He, Xi-Xin; Lei, Ling-Fang; Zhong, Ying; Wang, Zhi-Fang; Ye, Wen-Cai (Planta Medica, 2013)
Six new triterpenoid saponins, psychotrianosides A–F (1–6), and two known triterpenoid saponins, psychotrianoside G (7) and ardisianoside D (8), were isolated from Psychotria sp. Their structures were determined mainly by spectroscopic methods. The cytotoxic activities of 1–8 against five human cancer cell lines (MDA-MB-231, MCF-7, MCF-7/ADM, HepG2, and HepG2/ADM) are reported for the first time. Psychotrianoside C (3) showed the most potent antiproliferative activity among these saponins, and the IC50 value of 3 against MDA-MB-231 was 2.391 ± 0.161 µM. Compound 3 was also found to induce apoptosis.
Keywords: Rubiaceae; Psychotria sp.; triterpenoid saponins; antiproliferative